Kajian Filosofis Tradisi Slametan Jum’at Legi Di Pura Penataran Giri Purwo Desa Kalipait Kecamatan Tegaldlimo Kabupaten Banyuwang - Astu Arya Putra; Gede Mahardika; I Made Gami Sandi Untara (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The Slametan Friday Legi tradition at Pura Penataran Giri Purwo is a tradition that is continuously carried out and is a legacy from the ancestors in Kalipait Village. The uniqueness of this tradition lies in its implementation which is carried out by Slametan every Friday Legi together by the people of Kalipait Village at Penataran Giri Temple, Purwo. Based on this background, it can be formulated several problem formulations that will be discussed including: 1) Why is the Slametan Friday Legi Tradition held at Penataran Giri Purwo Temple, Kalipait Village, Kec. Purwoharjo, Kab. Banyuwangi? 2) What is the function of the Slametan Friday Legi tradition at Penataran Giri Temple, Purwo, Kalipait Village, Kec. Purwoharjo, Kab. Banyuwangi? 3) What are the implications of implementing the Slametan Friday Legi Tradition at Penataran Giri Purwo Temple to the Kalipait Village Community, Kec. Purwoharjo, Kab. Banyuwangi? The method used in this research is using qualitative methods with data collection techniques of observation, interviews and document studies. The theories that are the basis and are used to dissect the formulation of the problem include 1) religious theory used to dissect the second problem formulation, 2) structural functional theory used to dissect the third problem formulation, and 3) socio-structural theory used to dissect third problem formulation. This type of research is a qualitative research using data collection techniques in the form of interviews, observations, literature studies, and document studies. The process in data analysis will produce 1) The procession of the Slametan Jum'et Legi Tradition at the Penataran Giri Purwo Temple, Kalipait Village which includes: History of the Slametan Friday Legi Tradition, the process of implementing the Slametan Friday Legi Tradition at the Penataran Giri Purwo Temple, Kalipait Village, the meaning of using the means of the Slametan Friday Legi tradition. 2) The function of implementing the Slametan Friday Legi Tradition at Penataran Giri Temple, Purwo, Kalipait Village includes: religious functions, social functions, and harmonization functions. 3) The implications of the Slametan Friday Legi tradition at Penataran Giri Purwo Temple for the Kalipait Village Community include: spiritual and devotional implications, social implications, and economic implications.